Keteladanan Keluarga Kristiani Seturut Ajaran Amoris Laetitia Di Paroki Santo Yoseph Long Pahangai - Yunita Filadelvia Hurai Ibo; Wilfridus Samdirgawijaya; Hilario Didakus Nenga Nampar (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
This research aims to get an overview and describe the forms of exemplary Christian families according to the teachings of Amoris Laetitia in Santo Yoseph Long Pahangai Parish and to find challenges in providing role models to children. This research was conducted at Santo Yoseph Long Pahangai Parish using qualitative descriptive methods and the data collection techniques used were observation and interviews. The informants from this research were 12 people from marriage ages 10 to 15 years. Based on this research, it was found that parents have provided an example for their children. These forms emerge from within parents with full awareness of their responsibility as first and foremost educators. However, in implementing these forms of example, several obstacles and challenges arise from the parents and the children. The example of parents is very important for children, because everything starts at home, especially in family life. In this way, one day children will be able to follow in the footsteps of their parents' family example to prepare them for the future.